Technology assessment for emerging technology Meeting new demands for strategic intelligence - Robinson, Douglas K. R.. (OECD Science, Technology and Industry Policy Papers, 2023)
The rapid pace of technological change, coupled with a pressing need for solutions to address grand societal challenges and global crises, heightens the challenge for policy makers to develop science, technology and innovation policies at speed, in situations of high uncertainty and, in some cases, around potentially controversial technology fields. Technology assessment (TA) has a long history of providing decision-makers with timely strategic intelligence on emerging technologies. Current demands are pushing TA to evolve in order to fulfil diverse functions: to illuminate the societal, economic, environmental and other consequences of new technologies; to inform public opinion; and to guide research and development. Drawing on nine case studies, this report analyses the response of TA practices to these changing drivers and demands to support policies for new and emerging technologies. It also identifies a set of principles to guide good contemporary TA practice